Islamic sustainable finance: policy, risk and regulation - Billah, Mohd Ma'Sum (Routledge, Taylor & Francis Group, 2024)
The central idea of sustainability in the modern world is intricate and ever-changing. Closely related to the realm of finance and socioeconomic discussion, the phrase “sustainable impact finance” has become increasingly popular among bankers, practitioners, financial analysts, investors and the relevant experts seeking an impactful connection between the best financing mechanisms or tools and sustainable development related investments or projects.